The Effect of Hypoxia-Induced Exosomes on Anti-Tumor Immunity and Its Implication for Immunotherapy - Guo, Wenwen; Qiao, Tianyun; Dong, Bingwei; Li, Tian; Liu, Qiang; Xu, Xiaofeng (Frontiers in Immunology, 2022)
Hypoxia is a critical feature of solid tumors and is considered to be a key factor in promoting tumorigenesis and progression. Beyond inducing metabolic reprogramming of tumor cells to adapt to the hypoxic tumor microenvironment, hypoxia can also promote tumor growth by affecting the secretion of exosomes. Exosomes are nano-sized (30 150 nm in diameter) extracellular vesicles that can carry numerous substances including lipids, proteins, nucleic acids, and metabolites. Furthermore, hypoxia-induced changes in exosomes can also occur in various cells including stromal and immune cells. Besides promoting tumor invasion, angiogenesis, and drug resistance, the secretion of these altered exosomes has recently been found to negatively regulate anti-tumor immune responses. In this review, we focus on the hypoxia-induced altered secretion of various cellular exosomes and their subsequent effects on the tumor microenvironment, especially the anti-tumor immune system. Lastly, we also describe the recent advances in using exosomes as tumor therapeutics and in promoting anti-tumor immunity. In conclusion, ongoing discoveries in this field have brought new insights into hypoxic exosome-led immunosuppression, enabling the development of exosome-targeted therapeutics and elucidating their potential in combination with immunotherapy.